2009
DOI: 10.1293/tox.22.1
|View full text |Cite
|
Sign up to set email alerts
|

An Intratracheal Instillation Bioassay System for Detection of Lung Toxicity Due to Fine Particles in F344 Rats

Abstract: It is an urgent priority to establish in vivo bioassays for detection of hazards related to fine particles, which can be inhaled into deep lung tissue by humans. In order to establish an appropriate bioassay for detection of lung damage after particle inhalation, several experiments were performed in rats using quartz as a typical lung toxic particle. The results of pilot experiments suggest that Days 1 and 28 after intratracheal instillation of 2 mg of fine te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Notably, TISMO contains no iron component, therefore the iron accumulation is likely to have derived from an endogenous source in the body. In our previous studies in which TISMO fibers administered by intratracheal instillation to F344 rats (4 mg per rat) were used, only mild inflammatory reactions were observed compared to quartz particles in the lungs after 28 days (21,22). Results of other studies of TISMO administration by chronic inhalation also found limited inflammation in the lung (23,24).…”
Section: Discussionmentioning
confidence: 91%
“…Notably, TISMO contains no iron component, therefore the iron accumulation is likely to have derived from an endogenous source in the body. In our previous studies in which TISMO fibers administered by intratracheal instillation to F344 rats (4 mg per rat) were used, only mild inflammatory reactions were observed compared to quartz particles in the lungs after 28 days (21,22). Results of other studies of TISMO administration by chronic inhalation also found limited inflammation in the lung (23,24).…”
Section: Discussionmentioning
confidence: 91%
“…In animal models, inhalation of both nanosized CuO and nanosized ZnO were reported to induce severe acute pulmonary inflammation. In the case of CuO, depending on dose and exposure frequencies, an acute or more chronic inflammation was observed (Wang et al, 2008;Yokohira et al, 2009). Another study found that NP of ZnO and CuO may induce eosinophilic inflammation (Cho et al, 2010), and eosinophils play a key role in mediating asthma and other allergic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We have also employed quartz as a positive control for material induced lung inflammation in F344 rats and have established a bioassay model by intratracheal instillation for detection of lung toxicity due to fine particles in F344 male rats 18,26–28 . From these previous experiments in our laboratory, 0.1 mg quartz was concluded to be a sufficient dose to cause inflammation in the lungs of a mouse (estimated average body weight: 20 g) based on our previous findings for 1 mg quartz in F344 rats (estimated average body weight: 200 g) 26,27 .…”
Section: Discussionmentioning
confidence: 95%